2023
DOI: 10.1136/lupus-2022-000750
|View full text |Cite
|
Sign up to set email alerts
|

Risks of mortality and severe coronavirus disease 19 (COVID-19) outcomes in patients with or without systemic lupus erythematosus

Abstract: ObjectivesWe compared the outcomes of patients with or without systemic lupus erythematosus (SLE) who were diagnosed with coronavirus disease 19 (COVID-19) and evaluated factors within patients with SLE associated with severe outcomes.MethodsThis retrospective cohort study used the deidentified Optum COVID-19 electronic health record dataset to identify patients with COVID-19 from 1/1/2020 to 31/12/2020. Cases with SLE were matched with general controls at a ratio of 1:10 by age, sex, race and ethnicity and CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Major risk factors linked to a more severe infection were disease activity and GC use, together with use of mycophenolate and tacrolimus. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Major risk factors linked to a more severe infection were disease activity and GC use, together with use of mycophenolate and tacrolimus. 28 …”
Section: Discussionmentioning
confidence: 99%
“…However, the results of different studies are conflicting regarding the effects of immunosuppressive drugs on COVID‐19 severity. In the study by Bruera et al 1 including 687 SLE patients and 6870 controls, negative effects of COVID‐19 were associated with glucocorticoids, methotrexate, leflunomide, cyclosporine, and tacrolimus; but not with azathioprine, cyclophosphamide, or rituximab. Furthermore, belimumab had a protective effect against severe COVID‐19 1 .…”
Section: The Factors Possible Effects On Covid‐19 Outcomementioning
confidence: 96%
“…In the study by Bruera et al 1 including 687 SLE patients and 6870 controls, negative effects of COVID‐19 were associated with glucocorticoids, methotrexate, leflunomide, cyclosporine, and tacrolimus; but not with azathioprine, cyclophosphamide, or rituximab. Furthermore, belimumab had a protective effect against severe COVID‐19 1 . In contrast, Singh et al 30 reported that rituximab conferred 3–5 fold higher odds of intensive care unit admission and mechanic ventilation in RA, in a national cohort study including 69 549 RA patients.…”
Section: The Factors Possible Effects On Covid‐19 Outcomementioning
confidence: 96%
See 2 more Smart Citations